AB0704 Evaluation of nailfoldvideocapillaroscopy in familial mediterranean fever patients. (23rd January 2014) - Balkarli, A.; Ozkan, Ü.; Özhan, N.; Temel, S.; Cobankara, V.
Abstract : Background: Familial Mediterranean Fever (FMF) is an inflammatory disease characterized by synovitis and pleurotic attacks. It is an autosomal recessive disorder, and the exact etiology is unknown. 7% of patients can have Henoch-Schönleinpurpura and polyarthritis nodosa. Objectives: We aimed to determine microvascular abnormalities in FMF patients with nailfoldvideocapillaroscopy. Methods: We included non-smoker 29 FMF patients and 30 healthy individuals. Patients were reviewed about smoking, Raynaud's phenomena and ischemic ulcers. Patients who had comorbidities including hypertension, smoking and Raynaud's phenomena were not included in this study. A computerized form including demographic, clinical and para-clinical features was used to collect data. We used videocapillaroscope (x200) for capillaroscopic evaluation. Patients were put to hand rest (protection from trauma) 2 weeks before the capillaroscopic procedure and hands were held in room temperature at least 20 minutes on the day of the procedure.8 fingers excluding thumbs (total of 32 fields of one millimeter right and left from each finger median line) were evaluated independently by 2 doctors, and signs were recorded to patient follow-up form. We evaluated capillary quantity, microhemorrhage, ectasied capillaries (neat-not neat), megacapillaries, avascular space, bushy capillaries, meandering capillaries, neovascularization and bizarre capillaries with nailfoldvideocapillaroscopy. Ectasied capillaries were defined as capillary diameter >0.02 nm, megacapillaries as >0.05 nm, and microhemorrhage was defined as hemorrhage determined in at least two fingers without trauma. Results: Mean age of patients was 29.5±12 (16-60), disease starting age was 20.9±9.66 (7-49), and disease duration was 8.69±8 (1-33) years. We observed megacapillary and microhemorrage in one patient (3.44%), tortuosity in 11 patients (37.93%), and bizarre capillary in 7 patients (24.13%). No association was found between capillaryscopic pathologies and age, disease starting age, disease duration and clinical signs. Conclusions: Except one patient with microhemorrage and megacapillary, all signs we observed in this study were nonspecific capillaroscopic findings and did not explain the importance of these in FMF patients. Further studies can be made to understand videocapillaroscopic signs with larger study group. Disclosure of Interest: None Declared